O plano de eliminação da hanseníase no Brasil em questão: o entrecruzamento de diferentes olhares na análise da política pública - Figueiredo, Ivan Abreu (2006)
Evaluation of the first ten years (1995-2004) of validity of the Brazilian Leprosy Elimination Plan (LEP) based upon the crossing of looks from different subjects in the analysis of this public policy. The historical course of the actions opposed to leprosy in social and sanitarian imagination is described, emphasizing processes of building and deconstructing stigma. The researcher s route of gaze conversion in the articulation of Health and Social Sciences is told, describing the composition of the methodological investigation path under the perspective of complementarities between the epidemiological approach and looking at the new world of senses and meanings of the narrative interview. Controversies surrounding the aim of elimination of leprosy as a public health problem defended by WHO (World Health Organization) and adopted by the Brazilian Health Ministry (BHM) as a mainstay of the public policy opposed to this endemic are exposed. Throughout the analysis, the frailty of the elimination concept defended by WHO/BHM is showed, based upon statistical time trend analysis of epidemiological and operational indicators as well as testimonies from different subjects involved in LEP. Personal, family and professional repercussions of being a Hansen s disease patient are approached, considering as a starting point the threat of breaking social ties, outlining processes of unbelonging. The multi drug therapy (MDT) treatment is described, singularizing fortuitous damages brought to the clients, including considerations about patients and physicians different cure times for and meanings of treatment interruption. The restricted perspective of the statistic leprosy elimination aim is contrasted with the course of growing breadth of leprosy control actions in Brazil. The articulation of health activities opposed to leprosy with the effort of humanized care of the clients now occurring in BHM is glimpsed.